HADE Coffee Information System Strategy Planning Using The Swot Analysis Method - Julianti, Putri Amelia; Wahyuningsih, Poni; Susilawati, Susilawati; Safitri, Nenden Intan; Nugraha, Aditya (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2024)
The coffee business sector is one of the promising businesses with the current increase in coffee lovers. Thorough information system strategy planning can be used as a reference to gain a competitive advantage for Hade Kopi. The aim of this research is to analyze environmental factors to determine their strengths, weaknesses, opportunities and threats and also determine the determining factors for success so that a proposal for a planning strategy information system can be prepared in the form of a portfolio of future applications at Hade Kopi. In this research, the author conducted observations and interviews directly with Hade Kopi, as well as reading library sources. In compiling this research the author used Ward and Peppard's approach by analyzing the Internal Business Environment, External Business Environment, Internal IS/IT Environment, and External IS/IT Environment using several analytical methods, namely Value Chain, PEST Analysis, Porter's Five Forces, McFarlan Strategic Grid, and SWOT Analysis. The final result of this research is a proposal for preparing Hade Kopi's future IS/IT strategy which includes information system needs, information technology needs, future business processes, and Hade Kopi's future application portfolio